Pertumbuhan Ekonomi dan Ketimpangan Antar Kecamatan di Kabupaten Banyumas, 1993-2000 - Sutarno Sutarno; Mudrajad Kuncoro (Economic Journal of Emerging Markets, 2003)
This research attempts to identify the nature of economic growth and to understand disparity among of sub-districts in Banyumas regency. The tools of analysis are Klassen typology, Williamson index, entropy Theil index, trend and Pearson correlation.Klassen typology shows that Banyumas sub-district can be classified into four types: high growth and high income, high income but low growth, high growth but low income, low growth and low income. Based on Williamson index and entropy Theil index, we found that disparity of gross regional domestic product per capita among sub-districts in Banyumas tended to increase over the period of 1993-2000. More importantly, our findings confirmed that Kuznets hypotesis could be found in Banyumas. Indeed, there has been a negative correlation between Williamson index or entropy Theil index with GRDP growth.